POLITICAL STRATEGY OF MUHAMMAD AL-FATIH ON THE MOVIE “BATTLE OF EMPIRES FETIH 1453” IN CONQUERING THE CITY OF CONSTANTINOPEL - Adi Dharma Bagaskara (Metakom, 2018)
There are 15 political strategies used by the Sultan Muhammad Al-Fatih to conquer the city of Constantinopel. This research uses descriptive-qualitative research using Roland Barthes semiotics theory to know the meaning of denotation, connotation and myth in film. The object of research was the movie “Battle of Empires Fetih 1453” directed by Faruk Aksoy with the focus of analyzing the political strategy of Sultan Muhammad Al-Fatih in the form of scene in the film “Battle of Empires Fetih 1453”. Peter Schroeder’s political strategy was used to determine the scene of political strategy. The findings of the scene will be analyzed using semiotics theory ti find the meaning of denotation, connotation and myth. Keywords : Semiotics Roland Barthes, Movie Battle of Empires Fetih 1453, Muhammad Al-Fatih, Political Strategy